Anti-saccade as a tool to evaluate cognitive impairment in vestibular migraine - Lu, Lingmei; Ni, Wenyu; Liu, Yin; Sun, Li; Li, Fei (Frontiers in Neurology, 2024)
Background Vestibular migraine (VM), an intricate subtype of migraine, amalgamates the dual attributes of migraine and vestibular disorders. In clinical settings, individuals with VM frequently articulate concerns regarding the manifestation of subjective cognitive impairment. This cognitive dysfunction is intricately linked with diminished mobility, heightened susceptibility to falls, and increased absenteeism in afflicted patients. Consequently, comprehending the features of cognitive impairment in VM patients holds potential clinical significance. The pursuit of rapid and objective methods for detection and assessment is foundational and prerequisite for efficacious cognitive management of VM patients. Methods The study encompassed 50 patients diagnosed with vestibular migraine and recruited 50 age-sex matched healthy controls. All participants underwent anti-saccade tasks, and cognitive evaluation was performed using the MMSE and MoCA to assess overall cognitive function. Additionally, RBANS scales were employed to measure specific cognitive domains. Results The VM patients and normal controls demonstrated statistical parity in terms of age, gender, education, weight, and BMI, with no significant differences observed. Analysis of cognitive scores divulged a marked increase in the incidence of Mild Cognitive Impairment (MCI) in VM patients compared to Healthy Controls (HCs). Both MMSE and MoCA scores were notably lower in VM patients compared to their healthy counterparts. The RBANS cognitive test indicated significant impairment in immediate memory, visuospatial construction, language, attention, and delayed memory among VM patients. Notably, the Trail Making Test and Stroop Color-Word Test revealed compromised processing speed and executive function cognitive domains. The anti-saccadic task highlighted significantly elevated anti-saccadic latency and frequency of direction errors in vestibular migraine patients. Symptom severity, illness duration, and episode frequency in VM patients positively correlated with counter-scanning errors and negatively correlated with cognitive performance across diverse cognitive domains. Conclusion VM patients exhibit cognitive decline across multiple cognitive domains during the interictal period. This cognitive impairment may not be fully reversible, underscoring its potential clinical significance for cognitive management in VM patients. The sensitivity of anti-saccade tasks to the cognitive status of VM patients positions them as promising objective indicators for diagnosis, intervention, and evaluation of cognitive impairment effects in VM in future applications.